Wheat pill poisoning: complications and management - Hassan Ur Rehman; Valeed Bin Mansoor; Fibhaa Syed; Mohammad Ali Arif; Ayesha Javed (Journal of the Pakistan Medical Association, 2021)
Wheat pill (zinc or aluminum phosphide) is used as rodenticide in wheat and rice storage reservoirs also known as rice pill. In developing countries like Pakistan there has been an increase in the number of aluminum phosphide (wheat-pill) poisoning with suicidal intent due to easy accessibility. It has high mortality rate, with no antidote available. A young female presented with wheat pill poisoning in June 2019, upon arrival she had classical signs and symptoms of wheat pill poisoning although during her stay she developed cardiac arrythmias leading to shock, Hematuria, Pleural effusion, and hyperglycemia due to acute pancreatitis. Due to the appropriate recognition and management of complications, patient was able to recuperate. felicitous transfer to Intensive Care Unit and prompt recognition of complications can lead to virtuous outcomes. We recommend that there should be nationwide cognizance campaign regarding the lethal consequences of wheat-pill consumption by humans and proper Continuous...